Newborn Screening for Cystic Fibrosis: A Qualitative Study of Successes and Challenges from Universal Screening in the United States - Marci K. Sontag; Joshua I. Miller; Sarah McKasson; Amy Gaviglio; Stacey L. Martiniano; Rhonda West; Marisol Vazquez; Clement L. Ren; Philip M. Farrell; Susanna A. McColley; Yvonne Kellar-Guenther (MDPI AG, 2022)
Cystic fibrosis (CF) newborn screening (NBS) was universally adopted in 2009 in the United States. Variations in NBS practices between states may impact the timing of diagnosis and intervention. Quantitative metrics can provide insight into NBS programs (NBSP), but the nuances cannot be elucidated without additional feedback from programs. This study was designed to determine facilitators and barriers to timely diagnosis and intervention following NBS for CF. The median age at the first CF event for infants with CF within each state was used to define early and late states (n = 15 per group); multiple CF centers were invited in states with more than two CF centers. Thirty states were eligible, and 61 NBSP and CF centers were invited to participate in structured interviews to determine facilitators and barriers. Once saturation of themes was reached, no other interviews were conducted. Forty-five interviews were conducted (n = 16 early CF center, n = 12 late CF center, n = 11 early NBSP, and n = 6 late NBSP). Most interviewees reported good communication between CF centers and NBSP. Communication between primary care providers (PCPs) and families was identified as a challenge, leading to delays in referral and subsequent diagnosis. The misperception of low clinical risk in infants from racial and ethnic minority groups was a barrier to early diagnostic evaluation for all groups. NBSP and CF centers have strong relationships. Early diagnosis may be facilitated through more engagement with PCPs. Quality improvement initiatives should focus on continuing strong partnerships between CF centers and NBS programs, improving education, communication strategies, and partnerships with PCPs, and improving CF NBS timeliness and accuracy.